Bridging Indigenous and Western knowledge-systems in knowledge co-production with Amazonian Indigenous communities: a systematic realist review. Issue 1 (31st December 2023) - Weaver, Kaja
ABSTRACT: Researchers have sought to understand how Indigenous and Western knowledge systems can be bridged for development research to be (a) more inclusive of local actors and knowledge and (b) more relevant to the problems it aims to address. Research in Amazonian Indigenous contexts remains dominated by a 'Western' science struggling to accommodate bottom-up development research. This paper examines how Indigenous and Western knowledge is bridged in knowledge co-production with Amazonian Indigenous communities, and what outcomes such bridging incurs. The paper uses a systematic realist review analysing 22 studies. It finds that the bridging of Indigenous and Western knowledge, in co-production with Amazonian Indigenous communities, was based on partnership between Indigenous and scholarly communities. Emphasising mutual respect, power-sharing, and empowerment of Indigenous communities, this bridging contributes to generation of knowledge that is more legitimate and beneficial for all actors involved in the co-production process. However, the paper also observes a gap between knowledge co-production in theory and practice. Power-relations between Western scientists and Indigenous communities need to be further addressed in development research. More work is needed to enhance the legitimacy of knowledge, in order to further empower Indigenous communities to address local challenges according to their own contexts and needs.